Cell death/proliferation and alterations in glial morphology contribute to changes in diffusivity in the rat hippocampus after hypoxia-ischemia - Anderova, Miroslava; Vorisek, Ivan; Pivonkova, Helena; Benesova, Jana; Vargova, Lydia; Cicanic, Michal; Chvatal, Alexandr; Sykova, Eva (Journal of cerebral blood flow and metabolism, 2011)
To understand the structural alterations that underlie early and late changes in hippocampal diffusivity after hypoxia/ischemia (H/I), the changes in apparent diffusion coefficient of water (ADC(W)) were studied in 8-week-old rats after H/I using diffusion-weighted magnetic resonance imaging (DW-MRI). In the hippocampal CA1 region, ADC(W) analyses were performed during 6 months of reperfusion and compared with alterations in cell number/cell-type composition, glial morphology, and extracellular space (ECS) diffusion parameters obtained by the real-time iontophoretic method. In the early phases of reperfusion (1 to 3 days) neuronal cell death, glial proliferation, and developing gliosis were accompanied by an ADC(W) decrease and tortuosity increase. Interestingly, ECS volume fraction was decreased only first day after H/I. In the late phases of reperfusion (starting 1 month after H/I), when the CA1 region consisted mainly of microglia, astrocytes, and NG2-glia with markedly altered morphology, ADC(W), ECS volume fraction and tortuosity were increased. Three-dimensional confocal morphometry revealed enlarged astrocytes and shrunken NG2-glia, and in both the contribution of cell soma/processes to total cell volume was markedly increased/decreased. In summary, the ADC(W) increase in the CA1 region underlain by altered cellular composition and glial morphology suggests that considerable changes in extracellular signal transmission might occur in the late phases of reperfusion after H/I.
Keywords: Hypoxia; počet buněk; hypoxie; Diffusion; Male; Rats, Wistar; glióza; Reperfusion; Time Factors; ischemie mozku; konfokální mikroskopie; Cell Proliferation; Animals; potkani Wistar; tělesná voda; Neuroglia; časové faktory; Body Water; Immunohistochemistry; Microscopy, Confocal; mužské pohlaví; Imaging, Three-Dimensional; Diffusion Magnetic Resonance Imaging; krysa rodu Rattus; astrocyty; neuroglie; proliferace buněk; Brain Ischemia; Rats; zobrazování trojrozměrné; hipokampální oblast CA1; CA1 Region, Hippocampal; Extracellular Space; difuze; zvířata; Cell Count; buněčná smrt; reperfuze; Cell Death; difuzní magnetická rezonance; imunohistochemie; Gliosis; extracelulární prostor; Astrocytes